Survival and synchrony in digital images. About a certain topicality of the BilderAtlas of Aby Warburg (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2019)
Aby Warburg produced his BilderAtlas within the framework of the transformations of the technical image, especially cinema. The article relates concepts such as survival, anachrony and synchrony with the appearance of the kinetic image. The way of presenting the images in the BilderAtlas has points in common with the relational and topological logic of digital images. The operational dimension of the image, explored in the Warburgian project, also reappears in digital visual culture. The article defends the topicality of the BilderAtlas to understand the algorithmic condition of the current image, as well as to search for alternatives to the control strategies for which it serves as an instrument.
Keywords: Aby Warburg; Survival; Cinematic image; Synchrony; Algorithmic image